Faith in nation exclusionary origins of nationalism - Marx, Anthony W. (Oxford University Press, 2003)
"In a startling departure from a historical consensus that has dominated views of nationalism for the past quarter century, Marx argues that European nationalism emerged ... in the early modern era, as a form of mass political engagement based on religious conflict, intolerance, and exclusion. Challenging the self-congratulatory genealogy of civic Western nationalism, Marx shows how state-builders attempted to create a sense of national solidarity to support their burgeoning authority. Key to this process was the transfer of power from local to central rulers; the most suitable vehicle for effecting this transfer was religion and fanatical passions."